2000
DOI: 10.1038/sj.leu.2401804
|View full text |Cite
|
Sign up to set email alerts
|

Deletion of the multidrug resistance-associated protein (MRP1) gene in acute myeloid leukemia with inversion of chromosome 16 has no prognostic impact

Abstract: LeukemiaDeletion of the multidrug resistance-associated protein (MRP1) gene in acute myeloid leukemia with inversion of chromosome 16 has no prognostic impact TO THE EDITORAcute myelomonocytic leukemia with bone marrow eosinophilia (AML FAB M4Eo) is a distinct subtype of acute myeloid leukemia (AML) which is associated with the chromosomal inversion inv(16)(p13q22) resulting in fusion of the MYH11 gene on 16p13 with the CBF␤ gene on 16q22. 1 In prospective studies it has been shown that AMLs with inv(16) are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2001
2001
2005
2005

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 7 publications
1
2
0
Order By: Relevance
“…Furthermore, no effect on treatment outcome was observed, which could be explained by the fact that additional transporters, such as P-gp and MRP1 homologues, appeared to be expressed in these patient samples [189]. These findings were in agreement with the results described by Döhner et al, which also showed no prognostic impact of MRP1 deletion in inv(16) AML patient samples [161]. Therefore, the relatively favorable prognosis of inv(16) AML patients seems to be caused by factors other than deletion of the MRP1 gene.…”
Section: Mrp1 Deletionsupporting
confidence: 85%
“…Furthermore, no effect on treatment outcome was observed, which could be explained by the fact that additional transporters, such as P-gp and MRP1 homologues, appeared to be expressed in these patient samples [189]. These findings were in agreement with the results described by Döhner et al, which also showed no prognostic impact of MRP1 deletion in inv(16) AML patient samples [161]. Therefore, the relatively favorable prognosis of inv(16) AML patients seems to be caused by factors other than deletion of the MRP1 gene.…”
Section: Mrp1 Deletionsupporting
confidence: 85%
“…[8][9][10][11][12][13][14][15] So far, no deletion has been reported in patients with t(15;17) or t(8;21)AML, but only 14 patients with t(8;21) had been tested. 15 Using a dual-fusion probe, we have analyzed 65 patients with AML and t(8;21), and found deletions 5Ј to the ETO breakpoint in 9% (6/65) of them.…”
Section: Discussionmentioning
confidence: 99%
“…Although these chromosomal rearrangements appear as reciprocal translocations, it has been reported that some of them were associated with submicroscopic deletions in a significant number of cases. [8][9][10][11][12][13][14][15] Moreover, at least in the CML model, these deletions may be associated with a specific poorer prognosis. 9 …”
Section: Introductionmentioning
confidence: 99%